Where the jobs are - Dearie, John
A guide to ending America's jobs emergency by accelerating the true engine of job creation start-ups Four years after the end of the Great Recession, 23 million Americans remain unemployed, underemployed, or have left the workforce discouraged. Even worse, Washington policymakers seem out of ideas. Where the Jobs Are: Entrepreneurship and the Soul of the American Economy shows how America can restore its great job-creation machine. Recent research has demonstrated that virtually all net new job creation in the United States over the past thirty years has come from businesses less than a year old true "start-ups." Start-up businesses create an average of three million new jobs each year, while existing businesses of any size or age shed a net average of about one million jobs annually. Unfortunately, the vital signs of America's job-creating entrepreneurial economy are flashing red alert. After remaining remarkably consistent for decades, the rate of new business formation has declined significant in recent years, and the number of new jobs created by new firms is also falling. In Where the Jobs Are, the authors recount the findings of a remarkable summer they spent traveling the country to meet and conduct roundtables with entrepreneurs in a dozen cities